Evaluating the collection, comparability and findings of six global surgery indicators. Issue 2 (20th December 2018) - Holmer, H; Bekele, A; Hagander, L; Harrison, E M; Kamali, P; Ng-Kamstra, J S; Khan, M A; Knowlton, L; Leather, A J M; Marks, I H; Meara, J G; Shrime, M G; et al.
Abstract: Background: In 2015, six indicators were proposed to evaluate global progress towards access to safe, affordable and timely surgical and anaesthesia care. Although some have been adopted as core global health indicators, none has been evaluated systematically. The aims of this study were to assess the availability, comparability and utility of the indicators, and to present available data and updated estimates. Methods: Nationally representative data were compiled for all World Health Organization (WHO) member states from 2010 to 2016 through contacts with official bodies and review of the published and grey literature, and available databases. Availability, comparability and utility were assessed for each indicator: access to timely essential surgery, specialist surgical workforce density, surgical volume, perioperative mortality, and protection against impoverishing and catastrophic expenditure. Where feasible, imputation models were developed to generate global estimates. Results: Of all WHO member states, 19 had data on the proportion of the population within 2h of a surgical facility, 154 had data on workforce density, 72 reported number of procedures, and nine had perioperative mortality data, but none could report data on catastrophic or impoverishing expenditure. Comparability and utility were variable, and largely dependent on different definitions used. There were sufficient data to estimate that worldwide, in 2015, there were 2 038 947 (i.q.r. 1 884 916–2 281 776) surgeons, obstetricians and anaesthetists, and 266·1 (95 per cent c.i. 220·1 to 344·4) million operations performed. Conclusion: Surgical and anaesthesia indicators are increasingly being adopted by the global health community, but data availability remains low. Comparability and utility for all indicators require further resolution. Graphical Abstract: This paper examines the availability, comparability and utility of six global surgery indicators. Surgical and anaesthesia indicators are increasingly being adopted by the global health community, but data availability remains low. Comparability and utility for all indicators require further resolution. An update, and a plea for improvement